2020
DOI: 10.1111/eea.12913
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐release packing and chilling reduce host‐searching ability of the parasitoid Diachasmimorpha longicaudata used in the augmentative control of tephritid flies

Abstract: Diachasmimorpha longicaudata (Ashmead) (Hymenoptera: Braconidae) is a solitary parasitoid used in augmentative releases to control Tephritidae (Diptera) fruit flies of economic importance. Pre-release process includes packing adult parasitoids in cages at high densities and expose them to a temperature of 2 AE 2°C during 105 min. In this process, females' antennae may be damaged resulting in a reduction in their host-searching ability and fecundity. Here we measured, for five consecutive days after chilling, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Shelly et al ( Shelly et al, 2010 ) observed negative effects of chilling on the flight capacity and mating performance of C. capitata held at high densities, however, the mating performance was restored after 3 days of recovery. A recovery of host-searching abilities of the parasitoid Diachasmimorpha longicaudata following damages from chilling for packaging was also observed after 1–2 days ( Cancino et al, 2020 ). In tsetse flies, Diallo et al (2019) reported that chilling was one of the main factors negatively affecting the quality of the sterile flies, in terms of emergence rates and flight ability.…”
Section: Discussionmentioning
confidence: 94%
“…Shelly et al ( Shelly et al, 2010 ) observed negative effects of chilling on the flight capacity and mating performance of C. capitata held at high densities, however, the mating performance was restored after 3 days of recovery. A recovery of host-searching abilities of the parasitoid Diachasmimorpha longicaudata following damages from chilling for packaging was also observed after 1–2 days ( Cancino et al, 2020 ). In tsetse flies, Diallo et al (2019) reported that chilling was one of the main factors negatively affecting the quality of the sterile flies, in terms of emergence rates and flight ability.…”
Section: Discussionmentioning
confidence: 94%